THE IMPACT OF SLEEP DEPRIVATION ON THE PERFORMANCE OF SERVICES AND PASSES TO VOLLEYBALL PLAYERS - Artan Kalaja; Nora Deda; Julian Kraja (European Scientific Journal, ESJ, 2015)
“Why do we need to sleep?" From a study of Webb, 1975, related with sleep deprivation, it was concluded that people that were underwent experiment had difficulty in showing attention to the required tasks. The main purpose of the athletes and coaches is to achieve optimal performance during sporting events, so knowing the relation of important factors that have the effects of sleep deprivation on sports performances, it is necessary to recognise them. Loss of sleep can have profound effects on human performance. Volleyball players and coaches believe that adequate sleep is essential for peak performance. Total sleep deprivation has been shown to adversely affect many aspects of behavior, and psychological knowledge. Meeting the needs for sleep facilitates a person's ability to perform a variety of psychomotor work. Studies have shown that sleep deprivation ranging from 30 to 64 hours, significantly affects reaction time. Similar results were found for works that include higher levels of cognitive function. Some studies suggest that sleep deprivation up to 24 hours, there is no evidence that influences the performance of physical exercise, such as muscular, cardiovascular and respiratory power, which must answer the exercises, while some other studies suggested some temporary changes of these skills. Reaction time and anaerobic power are two important factors affecting the performance of many sports.